Proposta de protocolo de telemonitoramento sob demanda de sinais biomédicos usando internet das coisas, computação móvel e armazenamento em nuvem - Machado, Francisco Muller (2016)
This work shows a proposal for a data communication protocol integrating internet of things technologies, mobile computing and cloud storage, applied to on-demand remote monitoring physiological signals. The aim of this work was to acquire, transmit, store, receive and allow the on-demand visualization, keeping the integrity of the biomedical signals representation for medical analysis, without changing the mobility of the patient being monitored. The work uses an ECG channel to acquire the patient’s electrocardiography signal, which is linked via Bluetooth to a mobile computing device. The mobile computing device, with wireless internet access, sends the physiological signal through the proposed protocol to a safe base of cloud information storage, which can be accessed on demand by a specialist to do the medical evaluation. On-demand remote monitoring allows the specialist to visualize and analyze recent data, as if it were real time remote monitoring of the patient, and visualize and analyze previous data that are stored in the cloud, similar to an analysis of a previously made exam. The proposed protocol has information security features, keeping the integrity of the time representation of the physiological signal, even if the data are corrupted. The work involved the use of new technologies applied to the necessity of physiological signals record. These technologies are evolving. The patterns are not consolidated, and changes are made as new necessities are presented and new solutions developed. For this work, it was used a tablet as a computing mobile device. However, a smartphone could also be used. The protocol was used with an electrocardiography channel signal, which can be modified to attend other necessities, including other physiological signals. As a physiological signal, for this work, it was used an ECG simulator signal.